2017
DOI: 10.4054/demres.2017.36.8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of smoking-attributable mortality to life-expectancy differences by marital status among Finnish men and women, 1971-2010

Abstract: BACKGROUND Smoking is known to vary by marital status, but little is known about its contribution to marital status differences in longevity. We examined the changing contribution of smoking to mortality differences between married and never married, divorced or widowed Finnish men and women aged 50 years and above in 1971–2010. DATA AND METHODS The data sets cover all persons permanently living in Finland in the census years 1970, 1975 through 2000 and 2005 with a five-year mortality follow-up. Smoking-attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…However, the relationship between marital status and health behaviour remains unclear. On the one hand, recent research has suggested that being married is associated with engaging in healthier behaviours, such as consuming less nicotine (Cho et al 2008;Peltonen et al 2017) and alcohol (Duncan et al 2006;Reczek et al 2016). However, studies have consistently shown that being married can have negative effects on body weight (Averett et al 2008;Klein et al 2013;Sobal et al 2003;Umberson et al 2009) and physical activity (Kaplan et al 2001;Rapp/Schneider 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between marital status and health behaviour remains unclear. On the one hand, recent research has suggested that being married is associated with engaging in healthier behaviours, such as consuming less nicotine (Cho et al 2008;Peltonen et al 2017) and alcohol (Duncan et al 2006;Reczek et al 2016). However, studies have consistently shown that being married can have negative effects on body weight (Averett et al 2008;Klein et al 2013;Sobal et al 2003;Umberson et al 2009) and physical activity (Kaplan et al 2001;Rapp/Schneider 2013).…”
Section: Introductionmentioning
confidence: 99%
“…If so, does the magnitude of the protective effect of marriage differ by age and sex, and which subgroups of unmarried persons have the lowest life expectancy and active life expectancy? While life expectancy and healthy life expectancy by marital status have been examined in different populations, previous investigations had assumed that marital status would remain unchanged until death ( Martikainen et al, 2014 ; Kaprio et al, 1996 ; Peltonen et al, 2017 ). Therefore, these analyses likely overestimated the protective effect of marriage, resulting in the conclusion of a significant increase in life expectancy and healthy life expectancy for married persons.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, women are more likely to attempt to regulate their (male) partner's health habits and be successful in changing them (Berg and Upchurch 2007;Rook et al 2011;Umberson 1992;Westmaas, Wild, and Ferrence 2002), as well as providing emotional support within the marriage (Kiecolt-Glaser and Newton 2001). Unmarried men are more likely than their married counterparts to have unhealthy behaviours such as smoking, or to die of cardiovascular and external causes, while this difference is smaller for women (Hilz and Wagner 2018;Martikainen et al 2005;Peltonen et al 2017;Wang et al 2020). Men's health also tends to worsen more after divorce than women's, although women suffer more from the loss of income that follows (Leopold 2018).…”
Section: Consistent Mortality Gradientsmentioning
confidence: 99%